Integration of Geographic Information Systems in Determining Flood Risk Evacuation Routes in Medan City - Muhammad Farouq Ghazali Matondang; Meilinda Suriani Harefa; Rohani; Eni Yuniastuti; Mulhady Putra; Rozi Mahmuda; Tengku Abdillah Azis (MO.RI Publishing, 2026)
This study aims to map flood risk evacuation routes in Medan City using the Network Analysis method based on Geographic Information Systems (GIS). Medan City is a flood-prone area due to rapid urbanization, inadequate drainage systems, and land use changes. The data used include the 2024 flood risk map, road network, and evacuation shelter locations. The evacuation route analysis was conducted using ArcGIS 10.8 software with the Network Analyst feature to determine optimal evacuation routes that avoid flood-prone areas and facilitate evacuation to safe locations. The results show ten main evacuation routes covering various districts in Medan City. These routes were designed based on accurate spatial data considering road conditions and flood risk zones. This evacuation route mapping is expected to serve as an important reference for local government and related agencies in planning flood disaster mitigation strategies and enhancing community safety. The GIS and Network Analysis approach proves effective as a planning tool for disaster evacuation by comprehensively considering geographical variables and transportation networks.